La química del café, una taza para quimiofóbicos - Ortega-San-Martin, Luis (2025)
This editorial in Revista de Quimica highlights a new article in the series "Chemistry on your Plate," dedicated to the chemistry of the processes involved in processing coffee beans into ready-to-drink beverages. Also featured in this first issue are other articles focused on biocosmetics and green synthetic fuels.